Perancangan Ruang Kolaboratif sebagai Wadah bagi Komunitas Keatif di Denpasar - Ida Bagus Alit Arinata; Ni Putu Ratih Pradnyaswari Anasta Putri; Ni Wayan Meidayanti Mustika (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2022)
According to the Ministry of Trade of the Republic of Indonesia, it is stated that the creative economy or creative industry is an industry created from the main production sources, namely creativity and skills from individuals who can provide a job or increase welfare through the work and utilization of creative power and creativity. According to the Denpasar City Tourism Office, there are 68 creative communities in Denpasar with various fields of activity, but Denpasar City lacks facilities for these creative communities to show their creativity and exchange ideas. This problem prompted the author to create a facility that can accommodate the activities of the creative community in the city of Denpasar. This facility will be designed using a Biophilic Architecture approach. The author uses a biophilic approach to make visitors feel more productive, creative and healthy. According to Nelly Shafik Ramzy (2014) Biophilic architecture is an innovative approach that opens the way to a nature-based dialogue between architectural space and the set of human innate affiliations, where natural forms and patterns play the role of vocabulary and grammar of composition. In this approach, incorporating Nature into the built environment is not a luxury, but a sound economic investment in Health and productivity.